New progress of regulations and judicial practice of intellectual property - Cheng, Deli; Yu, Xinmiao; Bacher, Klaus (Judge) (Springer, 2025)
This open access book brings together two types of cases at home and abroad. One is the latest influential cases in the field of intellectual property rights in the past three years, and the other is the classic intellectual property cases in the world. The types of cases involve typical cases in the fields of patents, trademarks, copyrights, unfair competition, etc., involving a wide range of intellectual property laws and a complete range of categories. Some cases have been a sensation, and some legal issues have been raised or clarified for the first time in relevant judgments. Many cases not only have a wide range of social influence but also have typical legal application significance. Many cases involve facts and legal issues that go beyond the case and the adjudication itself and have greater reference significance. At the same time, we also attached the different opinions of some case judgments, such as the Concurring Opinion and the Dissenting Opinion in the US judgment, reflecting the different understandings of different judges on the application of the law. This part is also very meaningful.